2008
DOI: 10.1111/j.1600-051x.2008.01248.x
|View full text |Cite
|
Sign up to set email alerts
|

5‐year clinical experience with BTI® dental implants: risk factors for implant failure

Abstract: Implant staging and the use of special techniques are risk factors for implant failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 22 publications
3
54
0
5
Order By: Relevance
“…19 Because periodontal disease is widely recognized as a risk factor for peri-implantitis and implant failure, 20,21 the higher prevalence of periodontal disease in males may explain the outcome of the study. Anitua et al 22 reported significantly lower survival for implants placed in the maxilla compared to the mandible. This difference might be the outcome of the less favorable osseous situation in patients requiring maxillary reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…19 Because periodontal disease is widely recognized as a risk factor for peri-implantitis and implant failure, 20,21 the higher prevalence of periodontal disease in males may explain the outcome of the study. Anitua et al 22 reported significantly lower survival for implants placed in the maxilla compared to the mandible. This difference might be the outcome of the less favorable osseous situation in patients requiring maxillary reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Yan etkiler enderdir ve sinir veya damarlara hasar gibi lokal reaksiyonlar ile sınırlıdır. Enjeksiyon bölgesinde skar doku oluşumu ve kalsifikasyon rapor edilmiştir (7) .…”
Section: Platelet-zengin Plazma Uygulamada Istenmeyen Etkilerunclassified
“…Anitua et al (2008) Estudio experimental, seguimiento clínico a un grupo de pacientes por 5 años El hábito de fumar, la posición del implante, la puesta en escena de implantes (los implantes de dos fases) y la aplicación de técnicas especiales fueron estadísticamente correlacionada con una menor supervivencia del implante.…”
Section: Ensayo Clínico Aleatorizadounclassified